2017
DOI: 10.1063/1.5016727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions on the cell morphology distribution in foamed injection molded PLA samples

Abstract: Abstract. Foam injection molding uses physical blowing agents under high pressure and temperature to produce structural foams having a cellular core and a compact solid skin. This technology is particularly interesting for biodegradable polymers, which often present a very narrow processing window, with the suitable processing temperatures close to the degradation conditions. The addition of a supercritical gas can lead to the reduction of both the viscosity and the glass transition temperature of the polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the examined literature, only a few publications on the foam injection molding of PLA with CBAs can be found [ 75 , 96 ]. Common physical blowing agents used for foam injection molding of PLA include N 2 [ 74 , 90 , 92 ] and CO 2 [ 58 , 76 , 246 ]. As far as the data given in the publications about injection-foamed PLA (cf.…”
Section: Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the examined literature, only a few publications on the foam injection molding of PLA with CBAs can be found [ 75 , 96 ]. Common physical blowing agents used for foam injection molding of PLA include N 2 [ 74 , 90 , 92 ] and CO 2 [ 58 , 76 , 246 ]. As far as the data given in the publications about injection-foamed PLA (cf.…”
Section: Processesmentioning
confidence: 99%
“…Intensive work on FIM of PLA with nitrogen was carried out by the group of Pantani and Volpe [ 89 , 90 , 92 , 93 , 95 ]. In an early work, they pointed out that higher injection flow rates resulted in a more homogeneous cell morphology and density reduction along the flow path.…”
Section: Processesmentioning
confidence: 99%
“…The few examples found used Azodicarbonamide [119,120]. The main PBAs used in foam injection moulding include CO 2 [121,122] and N 2 [123][124][125][126]. Nitrogen has a higher cell nucleating force, although it shows a lower solubility in polymers compared to carbon dioxide [53].…”
Section: Foam Injection Mouldingmentioning
confidence: 99%
“…Different works have reported the use of SFCs as foaming agents for PLA. Nitrogen was used for injection molding [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] and batch foaming [ 72 ]. However, Li et al [ 73 ] showed that the solubility of CO 2 in PLA is approximately ten times that of N 2 .…”
Section: Introductionmentioning
confidence: 99%